2007
DOI: 10.1103/physrevb.76.155427
|View full text |Cite
|
Sign up to set email alerts
|

Kondo effect in transport through molecules adsorbed on metal surfaces: From Fano dips to Kondo peaks

Abstract: The Kondo effect observed in recent STM experiments on transport through CoPc and TBrPP-Co molecules adsorbed on Au(111) and Cu(111) surfaces, respectively, is discussed within the framework of a simple model (Phys. Rev. Lett. 97, 076806 (2006)). It is shown that, in the Kondo regime and by varying the adequate model parameters, it is possible to produce a crossover from a conductance Kondo peak (CoPc) to a conductance Fano dip (TBrPP-Co). In the case of TBrPP-Co/Cu (111) we show that the model reproduces the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Moreover, It has been theoretically shown that the local DOS of the substrate, q m , is reduced with the growth of the molecular assembly. [147] The variation of the Kondo resonance with the chain formation was investigated for Co-(5,5-Br2-Salophen) molecules. [131] The 1D molecular chain is formed by removing Br atoms of each molecule and forming covalent bonds between the molecules.…”
Section: Molecular Ordering and Kondo Resonancementioning
confidence: 99%
“…Moreover, It has been theoretically shown that the local DOS of the substrate, q m , is reduced with the growth of the molecular assembly. [147] The variation of the Kondo resonance with the chain formation was investigated for Co-(5,5-Br2-Salophen) molecules. [131] The 1D molecular chain is formed by removing Br atoms of each molecule and forming covalent bonds between the molecules.…”
Section: Molecular Ordering and Kondo Resonancementioning
confidence: 99%
“…The differential conductance was calculated by means of a thoroughly tested finite U slave bosons ͑SB͒ approach 13,[18][19][20][21][22] and by exact solutions of small clusters that are finally embedded with the leads through appropriate selfenergies ͓"embedded cluster approximation" ͑ECA͒ see Ref.…”
Section: Conductance Calculationsmentioning
confidence: 99%
“…The spectroscopic operating mode of STM, the STS can be applied to investigate many-body effects on substrate-supported adatoms [61][62][63][64][65][66][67][68], and molecules [69][70][71], where Fano resonances [72] contain characteristic information about the Kondo physics. SP-STS has recently been used to find inversion of spin polarization above magnetic adatoms [73][74][75], and the effect has been explained theoretically [76].…”
Section: Introductionmentioning
confidence: 99%